Signal of candidate loci involved in wing color pattern in A Heliconius cydno hybrid zone in Cauca Valley (Colombia) (2010)
Heliconius butterflies exhibit a high level of radiation with numerous species that vary in its wing color pattern forms. The importance of these patterns in ecological speciation has been recently documented among these mimetic butterflies. However, the genes responsible for such variation are just starting to be identified in some races and specific populations from Costa Rica and Ecuador, but not in Colombia. Here, a wide genome scan was performed using AFLP (Amplified Fragment Length Polymorphisms), as a new way to approach and detect the signal of candidate genes involved in the production of adaptive traits such as color pattern loci, in natural populations of an H. cydno hybrid zone in Cauca valley (Colombia). By performing an AFLP genome scan, a total of 562 polymorphic sites were found using eight different primer combinations, among which only two where related to color pattern elements, loci Sb and Yb, and could be considered as possible candidates linked to these genes. These results show the utility of AFLPs in finding divergence regions that control characters that may be important in ecological speciation. This and future findings could be used to corroborate if the regions associated with the genes that determine color pattern in Colombian populations are the same as in Costa Rican and Ecuadorian populations.